Applicability of PD-L1 tests to tailor triple-negative breast cancer treatment in Brazil - Kátia Ramos Moreira Leite; Carlos Henrique Barrios; Antônio Carlos Buzaid; Débora Gagliato; Helenice Gobbi; Fernando Soares (BMC, 2021)
Abstract Background Triple-negative breast cancer (TNBC) is a heterogeneous disease that represents 10-20% of breast cancer cases. The prognosis for advanced TNBC is usually poor, with a median overall survival of approximately 18 months or less. Main text New targeted therapies such as anti-PD-L1 agents are emerging as an option to treat advanced TNBC. A panel of 6 national experts with an active interest in breast cancer convened online. Panel members had either clinical or pathology experience in breast cancer. The experts pre-defined critical questions in the management of PD-L1 in TNBC, and a literature review was performed for selected topics before the online meeting. Conclusion The experts led active discussions involving a multidisciplinary team comprising pathologists and clinical oncologists. The meeting served to discuss the most relevant issues. A total of 10 critical questions for PD-L1+ TNBC were debated and are presented in this review. This article discusses the current landscape for PD-L1 tests in TNBC in Brazil.